The Impact of a Metacognitive Intervention using I.M.P.R.O.V.E. Model on Grade 7 Students’ Metacognitive Awareness in Mathematics - et.al, Napoleon A. Montero (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study sought to investigate the impact of a Metacognitive intervention on Grade 7 students’ Metacognitive awareness in Mathematics. Using Concurrent Action Research as the research design of the study, one heterogeneous Grade 7 class from a public high school in Metro Manila underwent a six-week Metacognitive Intervention using a structured Metacognitive instructional model called, I.M.P.R.O.V.E. (Introducing the new concepts; Metacognitive questioning; Practicing; Reviewing and Reducing difficulties; Obtaining mastery; Verification; and Enrichment). The quantitative aspect of the research included the assessment of the Metacognitive Awareness before and after the intervention period using the Jr. Metacognitive Awareness Inventory (Jr. MAI). On the other hand, student interviews, Focus Group Discussions (FGD) with the observers, and learners’ outputs were examined in the qualitative aspect of the research. Results revealed that there were large, and huge significant differences between the pre-test and post-test results of the Jr. MAI. Moreover, the intervention gained affirmative responses from the teacher observers and student participants as a good intervention tool to enhance students’ Metacognitive Awareness in Mathematics. Emergent issues on the utilization of the intervention were discussed such as: Questions that direct student learning; Enrichment of students’ Metacognitive experience; and Use of reflections in Mathematics. Recommendations on improving the model utilization were also discussed which included: selection of topics where the I.M.P.R.O.V.E. is appropriate to be used; and emphasis of objectives as “today’s target” in classrooms